Do Recent Experiences of Sexual Violence and Co-Occurring Depression and Anxiety Symptoms Predict Poorer Functioning One Year Later During the Transition to Young Adulthood?. Issue 1 (January 2022) - Davis, Jordan P.; Pedersen, Eric R.; Rodriguez, Anthony; Tucker, Joan S.; Seelam, Rachana; Shih, Regina; D'Amico, Elizabeth J.
Sexual violence (SV) is a public health concern for youth. Few longitudinal studies address how experiences of SV and co-occurring depression and anxiety symptoms in early young adulthood may contribute to poorer functioning in young adulthood. Using a sample of 2, 416 youth aged 18 to 20 (Time 1), we assessed past year SV and co-occurring depression and anxiety symptoms. One year later, when youth were between the ages of 20 and 22 (Time 2), participants indicated their functioning in four domains: physical health and sleep quality, substance use consequences, psychological functioning, and social functioning. Using latent class analyses, we found six participant classes at Time 1 based on SV experiences and co-occurring depression and anxiety symptoms. Classes were variable by participants' reported degree of SV experiences and co-occurring depression and anxiety symptomology. Longitudinal analyses indicated that youth in a class that experienced high levels of both SV and co-occurring depression and anxiety at Time 1 generally reported the poorest functioning in all key domains at Time 2. However, classes where participants reported greater depression and anxiety symptoms—most often in the presence of, but at times in the absence of, SV—were consistently associated with poorer functioning for physical health, psychological functioning, and social health. Classes where participants reported greater SV—in the presence of, but at times in the absence of, depression and anxiety symptoms—were associated with greater alcohol and marijuana consequences. Findings suggest prevention of SV, accessible counseling for those that have experienced SV, and screening to identify and intervene to address depression and anxiety may all be essential to help prevent poorer functioning in young adulthood.